2018
DOI: 10.4336/2018.pfb.38e201701524
|View full text |Cite
|
Sign up to set email alerts
|

Controle químico de plantas daninhas em povoamentos de restauração florestal

Abstract: Objetivou-se avaliar o emprego do tratamento químico, com herbicida a base de glifosato, na formação de povoamentos de restauração florestal em áreas com predominância de braquiária, em comparação ao controle mecânico. O tratamento químico foi realizado através de capina em faixas de 1,2 m, antes do plantio, e quando a braquiária apresentava altura média de 30 cm, aplicando-se glifosato na dose de 1,44 kg ha-1, nas entrelinhas. O tratamento com controle mecânico consistiu de capinas em faixas de 1,2 m nas linh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
(14 reference statements)
2
4
0
Order By: Relevance
“…Herbicide applications occurred in less number than mowing operations (Table 1), as also reported by Santos et al (2018). The greatest number of applications occurred in the chemical treatment, with mean of one intervention at every 4.0 months in the total experiment period.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…Herbicide applications occurred in less number than mowing operations (Table 1), as also reported by Santos et al (2018). The greatest number of applications occurred in the chemical treatment, with mean of one intervention at every 4.0 months in the total experiment period.…”
Section: Resultssupporting
confidence: 66%
“…Results are suggesting that herbicide application in total area is more effective than the remaining strategies adopted in this study. Santos et al (2018) evaluated the employment of using predominant glyphosate herbicide treatment and mechanical treatment only in the forest setting stands in forestry restoration areas highly infested by brachiaria grasses and reported similar results to this current study. The authors reported that for glyphosate herbicide applications, it were necessary up to 13 months and that at 30 months the plants growth in height and diameter were significantly higher in the chemical treatment, in parallel to the costing of the mechanical treatment to be nearly three times more expensive.…”
Section: -10supporting
confidence: 79%
See 2 more Smart Citations
“…and Urochloa decumbens, which can reach up to 1.5 m in height and are diffi cult to control (Weidlich, 2011;Ferreira et al, 2016). Therefore, in the fi rst months after planting, intensive mechanical and chemical weeding around seedlings are necessary to avoid and control the competition for light, water, and nutrients with native and exotic spontaneous plants (César et al, 2014;Santos et al, 2018). Weeding represents a signifi cant part of maintenance costs in forest restoration projects, and the procedures used to control the competition of tree seedlings with fastgrowing plants are sometimes ineffi cient and costly (Brancalion et al, 2009).…”
Section: Discussionmentioning
confidence: 99%